Fundamentals of plastic optical fibers - Koike, Yasuhiro (Weinheim, Germany : Wiley-VCH GmbH & Co. KGaA, 2015)
Annotation Polymer photonics is an interdisciplinary field which demands excellence both in optics (photonics) and materials science (polymer). However, theses disciplines have developed independently, and therefore the demand for a comprehensive work featuring the fundamentals of photonic polymers is greater than ever. This volume focuses on Polymer Optical Fiber and their applications. The first part of the book introduces typical optical fibers according to their classifications of material, propagating mode, and structure. Optical properties, the high bandwidth POF and transmission loss are discussed, followed by an outline on the propagating mode characteristics and how they affect the performances of the fiber. The second part of the book reviews conventional materials of POFs and gives an overview on fabrication methods. This is followed by a survey of characterization methods. Based on the characteristics of optical communication systems, the last chapter will concentrate on the many advantages of POF in link and network design. Written by a top expert in the field, this is an invaluable resource for semiconductor physicists, materials scientists, polymer chemists, electrical engineers, and those working in the semiconductor industry.
Includes bibliographical references and index.
Print version record.
Keywords: Plastic optical fibers; Photonics; Photopolymers; Photonics; Photopolymers; Electronic books